2010
DOI: 10.1007/s00213-010-1853-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific effects of methylphenidate (Ritalin) on cognitive ability and decision-making of ADHD and healthy adults

Abstract: Our data therefore demonstrates that (a) MPH is capable of enhancing specific aspects of cognitive performance and (b) this enhancement is not specific to ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
84
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 40 publications
2
84
0
5
Order By: Relevance
“…On the other hand, our results in healthy young adults are in line with a recent study of the effect of MPH in normal young adults for whom MPH had no effect on the TOVA. However, these authors also found the same result for their subjects with ADHD [13], a finding inconsistent with the bulk of literature confirming that the TOVA is sensitive to MPH in individuals with ADHD [24,25].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…On the other hand, our results in healthy young adults are in line with a recent study of the effect of MPH in normal young adults for whom MPH had no effect on the TOVA. However, these authors also found the same result for their subjects with ADHD [13], a finding inconsistent with the bulk of literature confirming that the TOVA is sensitive to MPH in individuals with ADHD [24,25].…”
Section: Discussionmentioning
confidence: 53%
“…In the second screening, subjects completed multiple questionnaires to identify these disorders and low-threshold clinical cutoff criteria were used. Thus, it is unlikely that undiagnosed individuals were included in the group, a phenomenon that may have contributed to positive results in other studies where less rigorous criteria were used [10,13]. In addition, the subjects received detailed instructions regarding each stage of the test to be certain that their performance would be optimal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems emerge when recent studies demonstrated that Ritalin's effect on cognitive performance is not exclusive to people with ADHD; it also has positive effects on normal individuals (Agay, Yechiam, Carmel, & Levkovitz, 2010). According to these studies, normal individuals who take Ritalin have been shown to perform better in some of the cognitive tests than those who do not use the drug (Agay et al, 2010).…”
Section: Potential For Abusementioning
confidence: 99%
“…According to these studies, normal individuals who take Ritalin have been shown to perform better in some of the cognitive tests than those who do not use the drug (Agay et al, 2010). Since the drug can have positive effects on both ADHD patients and normal individuals, it may propagate misdiagnoses of the disorder.…”
Section: Potential For Abusementioning
confidence: 99%